Inclusive education for sustainable development: Examining the Inclusive Education Policy of the Gambia 2016-2030 in attaining economic progress through creating Human Capital - Ceesay, Karamo; Sonko , Kebba Lang (JIAN (Jurnal Ilmiah Administrasi Negara), 2024)
Education as a fundamental right is a key player in the drive for economic posterity. It is widely seen as an essential foundation for sustainable development, which could serve as an agent for economic growth, societal progress and environmental sustainability. It is against this backdrop, that the national education policy 2016-2030 was formulated to transform the Gambia into an economically sustainable country. It is a focus of global attention because for societies to thrive, education should take centre stage where individuals regardless of their physical ability or economic status will be productive persons. However, as people possess different abilities in different ways, the attention of advocates across the world has called for justice within the education setting, advocating for the right of every individual to access education in a conducive environment free from all forms of discrimination. This study aims to examine the national education policy in enhancing inclusive education policy for economic growth and sustainable development. The qualitative study conducted semi-structured interviews to assess the progress of the policy in attaining economic growth amongst the youth, inclusion of persons with disabilities and its challenges. The results show that the policy has improved in terms of human capital development and mainstreaming of special needs children. However, there are challenges like unequal distribution of state funds amongst schools and special needs children not being given full attention.